Metabolomic profiling and antifungal potential of turmeric (Curcuma longa) root exudate against Ganoderma boninense - LIDYA KARLINA; SUWANDI SUWANDI; RAHMAD FADLI; A. MUSLIM; HARMAN HAMIDSON; CHANDRA IRSAN (Society for Indonesian Biodiversity, 2025)
Abstract. Karlina L, Suwandi S, Fadli R, Muslim A, Hamidson H, Irsan C. 2025. Metabolomic profiling and antifungal potential of turmeric (Curcuma longa) root exudate against Ganoderma boninense. Biodiversitas 26: 3600-3609. Ganoderma boninense, the causative agent of basal stem rot, significantly threatens oil palm cultivation. Turmeric (Curcuma longa) is a potential source of antifungal compounds for agricultural applications. This study investigates the antifungal properties of root exudates from four turmeric ecotypes (Palembang, Bandung, Surabaya, and Bangka) against Ganoderma boninense and employs untargeted metabolomics using LC-HRMS. The root exudates were collected from two-month-old plants grown in soil by incubating the roots in aerated sterile distilled water for 12 hours. The exudates were then filter-sterilized and directly used for antifungal assays and metabolomic analysis. The results revealed that turmeric root exudates at concentrations of 1.25%, 5%, and 20% inhibited G. boninense growth in a concentration-dependent manner, with the efficacy varying depending on turmeric ecotypes. The Palembang ecotype exhibited the strongest antifungal activity, with inhibition rates of 37.7% to 46.7%. The Bandung and Surabaya ecotypes showed moderate inhibition (10.3-36.2%), while the Bangka ecotype had weak effects. None of the turmeric exudates at concentrations between 1.25% and 20% promoted the growth of G. boninense. Metabolomic profiling played a crucial role in this study, identifying 193 metabolites, with 20 significant differentially accumulated metabolites in the inhibitory exudate group. Key metabolites such as azelaic acid, bis(2-ethylhexyl) phthalate, haplofungin C, menthyl acetate, and piptamine were identified, shedding light on their potential contribution to antifungal activity. These findings indicate that turmeric root exudates contain bioactive compounds that could be explored as eco-friendly biocontrol agents against G. boninense.